CARRIAGE OF MULTI-DRUG RESISTANT UROBACTERIA BY ASYMPTOMATIC PREGNANT WOMEN IN YENAGOA, BAYELSA STATE, NIGERIA - Onanuga, Adebola; Omeje, Maureen Chinelo; Eboh, Darlington Deboh (African Journal of Infectious Diseases (AJID), 2018)
Background: Urinary Tract Infections (UTIs) in pregnancy are associated with significant morbidity for both mother andbaby but its early detection and treatments can prevent unfavorable complications in pregnancy. This study thereforedetermined the prevalence of asymptomatic bacteriuria and antimicrobial resistance profile of the urinary bacteria amongpregnant women in Yenagoa, Bayelsa State, Nigeria.Materials and Methods: Mid-stream urine samples were collected from 201 apparently healthy pregnant women attendingantenatal clinics in Yenagoa. The samples were analyzed and the organisms identified using standard microbiologicalmethods. Haemolysin production by the organisms was screened and their antimicrobial susceptibility was performed usingstandard assay methods.Results: A high significant bacteriuria of 119 (59.2%) was predominantly recovered from the pregnant women in theirsecond and third trimesters. The bacteria isolated; Klebsiella pneumoniae, Pseudomonas aeruginosa, Escherichia coli andStaphylococcus species had 36 – 67% of haemolysin producers. The bacteria exhibited a very high resistance to most of theantibiotics tested but the resistance to ceftazidime, gentamicin and ciprofloxacin was 28 – 67%. All the Staphylococcusspecies exhibited 90% and 85% resistance to cefoxitin (methicillin resistant) and vancomycin respectively. An 89 - 100%of the bacteria exhibited multiple antibiotic resistance and 72.3% of the screened bacteria phenotypically expressedExtended-Spectrum Beta-lactamase production.Conclusion: The high prevalence of significant bacteriuria with high multi-drug resistance among the study pregnantwomen call for regular education on proper personal hygiene and the need for early screening for UTIs during antenatalclinics as means of controlling the spread of antibiotic resistant organisms and complications in pregnancy.